2019
DOI: 10.1161/circinterventions.118.007702
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Effectiveness of a Drug-Coated Balloon for the Treatment of Femoropopliteal Lesions

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 30 publications
9
91
0
3
Order By: Relevance
“…We acknowledge the presence of a transient mortality signal and this has been previously published within the SFA randomized trial data at years 2 and 3, 14,15 but is no longer evident beyond that period, 8 and is further diminished by obtaining more balanced and complete vital status data in this study. The lack of a correlation between paclitaxel exposure and mortality was further evident by the observation that there was no difference in cause of death in different treatment groups, and no specific patterns of non‐fatal events to suggest mechanism.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We acknowledge the presence of a transient mortality signal and this has been previously published within the SFA randomized trial data at years 2 and 3, 14,15 but is no longer evident beyond that period, 8 and is further diminished by obtaining more balanced and complete vital status data in this study. The lack of a correlation between paclitaxel exposure and mortality was further evident by the observation that there was no difference in cause of death in different treatment groups, and no specific patterns of non‐fatal events to suggest mechanism.…”
Section: Discussionmentioning
confidence: 65%
“…The IN.PACT SFA and IN.PACT Japan studies were similarly designed randomized trials of the IN.PACT Admiral paclitaxel drug‐coated balloon (DCB) that both met their primary efficacy endpoint of patency at 1 year 6,7 . In the IN.PACT SFA study, follow‐up at 2 and 3 years showed a higher mortality in the paclitaxel arm that diminished at years 4 and 5 of follow‐up 8 …”
Section: Introductionmentioning
confidence: 99%
“…While the study evaluated mid-term outcomes through 3 years, other studies (eg, IN.PACT SFA, THUNDER, AcoArt I) have followed participants up to 5 years. 24,28,29…”
Section: Limitationsmentioning
confidence: 99%
“…Drug-coated balloons (DCBs) were developed to overcome these limitations. Many randomized controlled trials(RCTs) [2][3][4][5][6] have shown consistent superior outcomes of DCBs over uncoated balloons in femoropopliteal lesions, with data up to 5 years for some studies [7][8][9][10]. But,their application in lower limbs is still insu cient.…”
Section: Introductionmentioning
confidence: 99%